2015
DOI: 10.1002/clc.22376
|View full text |Cite
|
Sign up to set email alerts
|

A Risk Score for No Reflow in Patients With ST‐Segment Elevation Myocardial Infarction After Primary Percutaneous Coronary Intervention

Abstract: Background: Many factors are associated with no-reflow (NRF) phenomenon in ST-segment elevation myocardial infarction (STEMI), including plasma glucose, age, and pre-percutaneous coronary intervention (PCI) thrombus score. Initial clinical assessment would benefit from accurate NRF prediction. This study aimed to develop a simple scoring system to predict the risk of NRF in patients undergoing primary PCI with STEMI. Methods: Baseline clinical and procedural variables were used for risk score development (the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 25 publications
1
40
0
9
Order By: Relevance
“…In their study, Yesin et al showed that SS II could predict no‐reflow . Wang et al also predicted no‐reflow in the model they developed …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In their study, Yesin et al showed that SS II could predict no‐reflow . Wang et al also predicted no‐reflow in the model they developed …”
Section: Discussionmentioning
confidence: 99%
“…In the above‐mentioned studies, the incorporation of laboratory parameters into the scores might be helpful for implementing post‐procedural measures. However, these parameters do not enable the calculation of a risk score before the procedure . Unlike the previous scoring systems, we believe that the use of demographic and angiographic parameters that could be evaluated faster enable a more rapid evaluation independent of laboratory parameters, and thus this score would be helpful before PCI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A two-sided p value < 0.05 was considered significant. Potential independent variables associated with no-reflow in previous studies [7,8] or significantly different between the no-reflow and normal reflow groups in our study were selected for univariate analysis. All the significant variables from the univariate analysis were entered into the multivariate logistic regression model to identify independent predictors for the development of the no-reflow phenomenon.…”
Section: Discussionmentioning
confidence: 99%